2013
DOI: 10.1158/0008-5472.can-12-4572
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Role of the Lipid Raft SK3–Orai1 Complex in Human Cancer Cell Migration and Bone Metastases

Abstract: The SK3 channel, a potassium channel, was recently shown to control cancer cell migration, a critical step in metastasis outgrowth. Here, we report that expression of the SK3 channel was markedly associated with bone metastasis. The SK3 channel was shown to control constitutive Ca 2þ entry and cancer cell migration through an interaction with the Ca 2þ channel Orai1. We found that the SK3 channel triggers an association with the Orai1 channel within lipid rafts. This localization of an SK3-Orai1 complex seemed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
191
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(224 citation statements)
references
References 31 publications
14
191
0
Order By: Relevance
“…It is becoming increasingly clear that ion transport proteins do not act in an isolated manner on their own, but that they act in networks of functionally cooperating units [13,63,114,115]. This is reflected by the concept of the migration-associated transportome that we recently introduced [9].…”
Section: Outlook and Clinical Perspectivesmentioning
confidence: 99%
“…It is becoming increasingly clear that ion transport proteins do not act in an isolated manner on their own, but that they act in networks of functionally cooperating units [13,63,114,115]. This is reflected by the concept of the migration-associated transportome that we recently introduced [9].…”
Section: Outlook and Clinical Perspectivesmentioning
confidence: 99%
“…Structure and biological activity of fucoxanthin and carotenoids in cancer cells [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Biological functions of carotenoids in cell membranes [19][20][21][22] Interaction of carotenoids with lipid rafts [23] Cell model to study the integration of xenobiotics into lipid rafts [24] Antioxidant and pro-oxidant activity of fucoxanthin in animal cells and tissues [25][26][27] Structure and function of lipid rafts in cell membranes [28,29] Targeting lipid rafts in cancer cells [30][31][32][33][34][35][36] Ion channels, lipid rafts and cancer cells [37,38] Lipid rafts, cytoskeleton, cancer cells invasivity and tumor angiogenesis [30,40] …”
Section: Reference Numbersmentioning
confidence: 99%
“…Subsequently, Chantôme et al (17) revealed a novel signaling pathway in which the interaction of ORAI1 with the SK3 channel, part of the family of Ca 2ϩ -activated K ϩ channels, elicited a constitutive and store-independent Ca 2ϩ signaling that promoted breast cancer cell migration and bone metastasis formation. The functional complex is localized in the lipid raft microdomains, and this localization is mediated by SK3 expression since its downregulation completely delocalized ORAI1 outside of the raft components (17).…”
Section: Activating Invasion and Metastasismentioning
confidence: 99%